Study of the Perceptions of Higher Education Students about the implementation of Pixton. - Navas-Romero, Cristina (My University, 2023)
Nowadays, there are different digital tools that educators can apply to teach writing more efficiently. These devices focus on using comics to encourage students’ engagement while they are learning a foreign language by means of technology. One of these software tools is Pixton. It is a digital application that permits the design of digital comic strips, and it offers chances for offering feedback, sharing, and downloading comic strips. It also provides easy access for teachers and students. Former studies have analysed the implementation of Pixton for teaching writing skills in the EFL classroom. They offer verification of the usefulness of this tool to teach EFL grammar, vocabulary and writing skills in the Latin American context. However, there is little formal investigation about Pixton as a tool for teaching Storytelling in the Spanish context. This study was conducted with the participation of second-year students of an English Didactics subject from the Degree of Primary Education at the University of Malaga. Scholars were required to use Pixton to create in groups a short story in English to be narrated in class –a Storytelling – which should be focus on students of the second cycle of Primary Education. The story could be made-up by the students, adapted from a tale, or copied from the web. After implementing the task, the undergraduates had to accomplish a survey online with the purpose of expressing their perceptions about the learning experience of using Pixton. The participating sample was made up of 72 male and female students from the 2022/2023 academic year. Results indicate great success and reception of the experience on the part of the students, despite they asserted that they never had previously used Pixton. Among the most outstanding responses, the main drawback detected by the students was the difficulty to work with different computers, since the tool only permitted to edit the comics individually.
Keywords: Estudiantes universitarios; Inglés - Estudio y enseñanza; Tecnología educativa; Pixton; Digital Tool; Higher Education; New Technologies; Storytelling